An Arabidopsis divergent pumilio protein, APUM24, is essential for embryogenesis and required for faithful pre‐rRNA processing. (20th November 2017) - Shanmugam, Thiruvenkadam; Abbasi, Nazia; Kim, Hyung‐Sae; Kim, Ho Bang; Park, Nam‐il; Park, Guen Tae; Oh, Sung Aeong; Park, Soon Ki; Muench, Douglas G.; Choi, Yeonhee; Park, Youn‐Il; Choi, Sang‐Bong
Summary: Pumilio RNA‐binding proteins are largely involved in mRNA degradation and translation repression. However, a few evolutionarily divergent Pumilios are also responsible for proper pre‐rRNA processing in human and yeast. Here, we describe an essential Arabidopsis nucleolar Pumilio, APUM24, that is expressed in tissues undergoing rapid proliferation and cell division. A T‐DNA insertion for APUM24 did not affect the male and female gametogenesis, but instead resulted in a negative female gametophytic effect on zygotic cell division immediately after fertilization. Additionally, the mutant embryos displayed defects in cell patterning from pro‐embryo through globular stages. The mutant embryos were marked by altered auxin maxima, which were substantiated by the mislocalization of PIN1 and PIN7 transporters in the defective embryos. Homozygous apum24 callus accumulates rRNA processing intermediates, including uridylated and adenylated 5.8S and 25S rRNA precursors. An RNA–protein interaction assay showed that the histidine‐tagged recombinant APUM24 binds RNA in vitro with no apparent specificity. Overall, our results demonstrated that APUM24 is required for rRNA processing and early embryogenesis in Arabidopsis. Significance Statement: Pumilio RNA‐binding proteins possess multiple tandem repeat Puf domains, and participate in RNA degradation and/or translation repression. Twentyfive Pumilios are found in Arabidopsis, however their functions are largely unknown. Here, we show that nucleolar Pumilio APUM24 is implicated in the processing of 27SB and 5.8S precursor rRNAs. The apum24 mutant embryo is lethal before globular stage, emphasizing the essential role of APUM24 during developmental process in Arabidopsis.